NSCLC, metastaticCheckMate 026: a phase 3 trial of nivolumab vs investigator's choice (IC) of platinum-based doublet chemotherapy (PT-DC) as first-line therapy for stage iv/recurrent programmed death ligand 1 (PD-L1)−positive NSCLC - Socinski, Mark A.; Steins, Martin (Annals of oncology, 2016)
© The European Society for Medical Oncology 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.comBackground: Nivolumab improves OS compared with docetaxel in previously treated NSCLC. In a phase 1 study (CheckMate 012), nivolumab showed promising activity and manageable safety as monotherapy and in combination with ipilimumab in treatment naive advanced NSCLC. CheckMate 026 (NCT02041533), an open-label, randomized phase 3 study, evaluated the efficacy of nivolumab vs IC PT-DC as first-line therapy in stage IV/recurrent PD-L1-positive NSCLC.Methods: Patients with histologically confirmed and previously untreated stage IV or recurrent NSCLC, ECOG PS 0-1, and PD-L1 positivity were randomized 1:1 to receive nivolumab 3 mg/kg IV Q2W or IC PT-DC (histology-based) Q3W (up to 6 cycles) until disease progression or unacceptable toxicity. Patients with EGFR/ALK mutations sensitive to targeted therapy were excluded. Patients on IC PT-DC...